Post and core: a new clinical perspective – myths and facts - Matos, Jefferson David Melo de; Nakano, Leonardo Jiro Nomura; Lopes, Guilherme da Rocha Scalzer; Silva, Jhenifer Rodrigues; Grande, Mateus Favero Barra; Marques, Ana Carolina; Ramos, Nathália de Carvalho; Vasconcelos, John Eversong Lucena de; Andrade, Valdir Cabral; Bottino, Marco Antonio; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Objective: The present study aims to describe a literature review on post and core restorations from a new clinical perspective in dentistry. Also, to define the best choice regarding the intraradicular retainer, material used, confection techniques and their possible failures, explaining the myths and the truths about them. Methodology: This literature review was conducted by leading health databases: Pubmed (https://www.ncbi.nlm.nih.gov/pubmed), SCIELO (www.scielo.org) e Google Scholar (https://scholar.google.com.br). The keywords for the textual search were: Denture, Partial, Fixed; Post and Core Technique; Dental Research; Dentistry. Inclusion criteria were: literature on the subject under study, literature of recent years, english and portuguese languages, laboratory and clinical studies, and systematic reviews. Literature Review: Post and core are defined as prosthetic elements that seek intraradicular retention to support prosthetic crowns or unitary restorations. The ideal shape of the intraradicular retainer should supplement the dental remnant, allowing the shape of a prepared tooth to receive a prosthetic crown. In conjunction of the dental remnant, they are responsible for dissipating and absorbing the forces developed during the chewing cycles, without deformation or damaging the minimal cement layer. Conclusion: The evolution of endodontic therapy enables a restoration with greater safety of treated teeth. However, it is necessary to consider the remaining dental structure, mainly because the posts do not provide reinforcement, only retention and resistance to the prosthetic crown.